Gender, local knowledge, and lessons learnt in documenting and conserving agrobiodiversity - Yianna Lambrou; Regina Laub (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2006)
This paper explores the linkages between gender, local knowledge systems and agrobiodiversity for food security by using the case study of LinKS, a regional FAO project in Mozambique, Swaziland, Zimbabwe and Tanzania over a period of eight years and now concluded. The project aimed to raise awareness on how rural men and women use and manage agrobiodiversity, and to promote the importance of local knowledge for food security and sustainable agrobiodiversity at local, institutional and policy levels by working with a diverse range of stakeholders to strengthen their ability to recognize and value farmers' knowledge and to use gender-sensitive and participatory approaches in their work. This was done through three key activities: capacity building, research and communication. The results of the LinKS study show clearly that men and women farmers hold very specific local knowledge about the plants and animals they manage. Local knowledge, gender and agrobiodiversity are closely interrelated. If one of these elements is threatened, the risk of losing agrobiodiversity increases, having negative effects on food security. Increased productivity, economic growth and agricultural productivity are important elements in poverty reduction. The diverse and complex agroecological environment of Sub-Saharan Africa requires that future efforts be based on more localized solutions while maintaining a global outlook. Food security will have to build much more on local knowledge and agrobiodiversity with a clear understanding of gender implications while keeping in mind the continuously changing global socioeconomic and political conditions. – gender ; biodiversity ; agrobiodiversity ; indigenous knowledge ; conservation ; sustainable management ; genetic resources ; participation ; livelihoods
Keywords: O13; O15; O17; O19; Q56; Q57; 330